AN ANALYSIS OF TABOO AND SWEAR WORDS IN TED 2 MOVIE - Meydli Dwiayu Garaga; M. Bahri Arifin; Chris Asanti (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
This study aims to identify the types and the functions of taboo and swear words used by the characters in Ted 2  movie. This study is conducted by using qualitative method and the findings are explained descriptively. Data were generated from the movie script, in the form of utterances, dialogues, and conversations that contain taboo and swear words. The findings revealed that most of taboo words used by the characters belong to religion. This study also find that the types of swear words in this movie are classified into two categories first are strong swear words and second is weak swear words. The strong swear words are verbalized by the characters showed the emotion and exclamation of annoyance. While the weak swear words which showed an exclamation of surprise. The reasons why the characters used swear words are to discredit someone/something, create attention, provoke and create interpersonal identification. Discrediting someone/something becomes the highest rank among four reasons. The characters in the movies often used it because they disagree with others, and the characters use swear words to protest for not complying with their wishes. Hence, learning and becoming more aware of how taboo and swear words are used in the literary work will help us improve our understanding of the linguistics phenomenon happened in the society.